Avoiding the Problem of the Commons in a Communist Society: The Role of Water Rights in the Enforcement of Environmental Law in China - Sonja Schiller (Washington University Journal of Law & Policy, 2009)
Part I of this Note examines the development of China’s modern legal system—including the recent unprecedented recognition of private property as a form of ownership—and describes challenges to systematic enforcement of environmental laws and regulations. Part I also discusses the history of water rights in China and the recent emergence of property interests in water vis-à-vis the sale and transfer of water permits. Part II analyzes how China’s 2007 Real Right Law gives legal protection to usufructuary rights in water permits and encourages the sustainable use of water, and the investment therein, that is fundamental to continued economic development. Parts III and IV propose that legal recognition of property interests in water will heighten enforcement of environmental laws by providing water pollution victims an alternate ground for standing to bring environmental litigation.
Keywords: Water rights; Commons; Environmental permits; Water pollution control; Water supply; China